2017
DOI: 10.1002/chem.201702224
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Synthesis of Perchlorinated Oligosilanes: A Fresh Look at an Old Reaction

Abstract: DedicatedtoProf. Nino Russo on theoccasiono fhis 70th birthday.Abstract: Ac ombined experimentala nd theoretical study of the high-temperature reactiono fS iCl 4 and elemental silicon is presented. The nature and reactivity of the product formed upon rapid coolingo ft he gaseous reactionm ixture is investigated by comparison with the defined model compounds cyclo-Si 5 Cl 10 , n-Si 5 Cl 12 and n-Si 4 Cl 10 .ADFT assessment provides mechanistic insight into the oligosilane formation. Experimental 29Si NMR invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 87 publications
1
14
0
Order By: Relevance
“…Along the reaction path the calculations indicate the intermediate formation of an unstable contact ion‐pair comprising a proton‐bridged cationic silicon species [Me 2 HSi−H−SiMe 3 ]Cl, which bifurcates into the two possible product channels (for details, see the Supporting Information). Overall, the reaction path shown in Scheme closely resembles the corresponding Cl 2 ‐induced Si−Si bond cleavage reported earlier . The competing chlorination of 3 proceeds through concerted H 2 elimination and HCl addition across the Si−H bond ( TS2 ).…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Along the reaction path the calculations indicate the intermediate formation of an unstable contact ion‐pair comprising a proton‐bridged cationic silicon species [Me 2 HSi−H−SiMe 3 ]Cl, which bifurcates into the two possible product channels (for details, see the Supporting Information). Overall, the reaction path shown in Scheme closely resembles the corresponding Cl 2 ‐induced Si−Si bond cleavage reported earlier . The competing chlorination of 3 proceeds through concerted H 2 elimination and HCl addition across the Si−H bond ( TS2 ).…”
Section: Methodssupporting
confidence: 66%
“…Overall, the reactionp ath shown in Scheme2 closely resembles the corresponding Cl 2 -induced SiÀSi bond cleavage reported earlier. [13] Cleavage/chlorination ratio [b] (Me 2 HSi) 2 (1)5.5 40 6M e 2 SiHCl (37) The competing chlorination of 3 proceeds through concerted H 2 elimination and HCl addition across the SiÀHb ond (TS2). As detailede arlier for the corresponding reaction of monosilanes [10] the activationbarrieriss ubstantially lowered by coordination of an ether molecule,w hichc ompensates the developing positive chargea tt he silicon center.…”
mentioning
confidence: 99%
“…The cation structure is undistorted and shows only very few weak contacts to the anions as shown by the Hirshfeld plot in Figure S10. The pentacation structure of 1 is related to the known (SiX 2 ) 5 pentamers (X=Cl, Br, I), which, in contrast, hold a folded Si 5 ring . However, it was shown that this ring may easily flatten .…”
Section: Figurementioning
confidence: 98%
“…Thep entacation structure of 1 is related to the known (SiX 2 ) 5 pentamers (X = Cl, Br, I), which, in contrast, hold afolded Si 5 ring. [21] However, it was shown that this ring may easily flatten. [22] Related phenomena were observed for the puckered (SiCl 2 ) 6 hexamer and its planar [Si 6 Cl 14 ] 2À chloride adduct.…”
mentioning
confidence: 99%
“…With respect to elementary reactions involving SiCl 2 , there have been many reports regarding molecules containing one or two SiCl 2 units, [11][12][13][14][15][16][17] but only two reports of molecules with more than two SiCl 2 units. 18,19 Mosecatteli et al evaluated the reaction rate constants of SiCl 2 forming cyclic-(SiCl 2 ) 4 via quantum chemical calculation using the B3LYP method with several basis functions: the amount of chlorinated silane polymers was negligibly small at 800 • C. 18 Neumeyer et al 19 studied the reaction mechanism for the formation of chlorinated silane polymers with up to eight SiCl 2 units using quantum chemical calculations with the RI-M06-L/6-311++G(2d,2p)//RI-M06-L/6-31+G(dp) method. The calculations for all SiCl 2 oligomer structures and their transition states revealed that the cyclic chlorinated silane polymer was produced by the oligomerization of SiCl 2 .…”
Section: Introductionmentioning
confidence: 99%